2009
DOI: 10.1097/rti.0b013e318190476f
|View full text |Cite
|
Sign up to set email alerts
|

“Reversed Halo Sign” of High-resolution Computed Tomography in Pulmonary Sarcoidosis

Abstract: We present a case of pulmonary sarcoidosis showing the "reversed halo sign" on high-resolution computed tomography (HRCT). A 27-year-old man presented with nonproductive cough and high fever lasting for 3 weeks. A chest radiograph showed multiple areas of consolidation and cavitary shadows in the lungs. The HRCT showed the reversed halo sign, a central ground-glass opacity surrounded by crescent or ring-shaped areas of consolidation. Moreover, miliary nodules were observed in the central ground-glass opacity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 13 publications
0
24
0
1
Order By: Relevance
“…The RHS is an atypical manifestation of the disease that has been reported in a few patients ( Figure 6) [29][30][31]. As reported in granulomatous infections, Kumazoe et al [30] described the presence of small nodules within the ground-glass area and around the outer areas of consolidation of the RHS in a patient with sarcoidosis. Associated CT findings included a large nodule in the left upper lobe, small subpleural nodules along the costal pleural surface and fissures, and mediastinal lymphadenopathy.…”
Section: Sarcoidosismentioning
confidence: 88%
“…The RHS is an atypical manifestation of the disease that has been reported in a few patients ( Figure 6) [29][30][31]. As reported in granulomatous infections, Kumazoe et al [30] described the presence of small nodules within the ground-glass area and around the outer areas of consolidation of the RHS in a patient with sarcoidosis. Associated CT findings included a large nodule in the left upper lobe, small subpleural nodules along the costal pleural surface and fissures, and mediastinal lymphadenopathy.…”
Section: Sarcoidosismentioning
confidence: 88%
“…The authors also noted the presence of miliary nodules within the central ground-glass opacities and around the outer areas of consolidation [23,24]. Several other authors subsequently emphasized the need to include the RHS within the spectrum of HRCT findings of pulmonary sarcoidosis [25][26][27].…”
Section: Organizing Pneumoniamentioning
confidence: 92%
“…Later, Kumazoe et al [24] reported the RHS in a case of sarcoidosis in which high-resolution computed tomography (HRCT) images showed multiple, central ground-glass opacities surrounded by crescentic or ringshaped areas of consolidation in both lungs. The authors also noted the presence of miliary nodules within the central ground-glass opacities and around the outer areas of consolidation [23,24].…”
Section: Organizing Pneumoniamentioning
confidence: 97%
“…The sign was previously described by Voloudaki et al [2] and by Zompatori et al [3]. However, recently this sign has also been described in various diseases, including pulmonary paracoccidioidomycosis [4], pulmonary zygomycosis, invasive pulmonary aspergillosis [5], lymphomatoid granulomatosis [6], Wegener's granulomatosis [7], lipoid pneumonia [8], pulmonary sarcoidosis [9], drug-induced interstitial pneumonitis [10] and cellular NSIP [11]. In the reversed halo sign of paracoccidioidomycosis and lymphomatoid granulomatosis, the central area of ground-glass opacity consisted of an inflammatory infiltrate involving mainly the alveolar septa, and the peripheral consolidation consisted of dense and homogeneous intra-alveolar inflammatory infiltrates.…”
Section: Discussionmentioning
confidence: 77%
“…In lipoid pneumonia, chronic inflammation with granulomatous organising lesions may lead to the reversed halo sign [8]. In pulmonary sarcoidosis, the sign consists of non-caseating granuloma with no evidence of organising pneumonia [9]. In these several cases, we assume that the reversed halo sign is mainly attributable to various stages of inflammation.…”
Section: Discussionmentioning
confidence: 99%